Effect of the surface oxide layer on shape memory effect and superelasticity of [011]-oriented Ti-50.1Ni single crystals - Chumlyakov, Yuri I.; Kireeva, Irina V. физик; Saraeva, Anastasia A.; Pobedennaya, Zinaida V.; Vyrodova, Anna V. (Metals)
Effect of the surface oxide layer on the shape memory effect (SME) and superelasticity (SE) after marforming (deformation in the martensitic state, followed by annealing at 713 K for 0.5 h in an inert helium gas and in dry air) was investigated on Ti-50.1Ni (at.%) single crystals, oriented along [011]-direction, under compression. Quenched [011]-oriented crystals of the Ti-50.1Ni alloy experience a one-stage B2-B190 martensitic transformation (MT) without SE under compression. Marforming leads to a two-stage B2-R-B190 MT and creates conditions for SE. A thin TiO2 oxide layer of 170 nm thick was formed on the sample surface upon annealing at 713 K for 0.5 h in dry air. In [011]-oriented crystals without and with an oxide layer, maximum of the SE value reached 4%, and the SME was 2.4 and 2.6%, respectively. Appearance of an oxide layer upon annealing in dry air: (i) reduces the stresses of B2-phase by 50 MPa from Md to 473 K; (ii) decreases Q = ds/d# from 6.5 GPa in crystals without an oxide layer to 2.0 GPa with an oxide layer and (iii) does not affect the SME and SE values.